2018
DOI: 10.2134/jeq2017.09.0369
|View full text |Cite
|
Sign up to set email alerts
|

A Field‐Scale Approach to Estimate Nitrate Loading to Groundwater

Abstract: The quantification of groundwater NO loading associated with a specific field or set of management practices so that groundwater quality improvements can be objectively assessed is a major challenge. The magnitude and timing of NO export from a single agricultural field under raspberry ( L.) production were investigated by combining high-resolution groundwater NO concentration profiles (sampled using passive diffusion samplers) with Darcy's flux estimation at the field's down-gradient edge (based on field-meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
25
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 45 publications
2
25
2
Order By: Relevance
“…Similarly, residual soil NO 3 –N in commercial raspberry fields in the Lower Fraser Valley, BC, which received manure (355 kg N ha −1 ), tended to be greater than for fields that received only mineral fertilizer (165 kg N ha −1 ) (Zebarth et al, 1998). In studies that used groundwater methods to estimate groundwater NO 3 –N loading, 174 kg N ha −1 was estimated under a manured raspberry field (Kuipers et al, 2014), whereas 80 kg N ha −1 was estimated under the current study field, which, at the time, had not recently received manure (Malekani et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, residual soil NO 3 –N in commercial raspberry fields in the Lower Fraser Valley, BC, which received manure (355 kg N ha −1 ), tended to be greater than for fields that received only mineral fertilizer (165 kg N ha −1 ) (Zebarth et al, 1998). In studies that used groundwater methods to estimate groundwater NO 3 –N loading, 174 kg N ha −1 was estimated under a manured raspberry field (Kuipers et al, 2014), whereas 80 kg N ha −1 was estimated under the current study field, which, at the time, had not recently received manure (Malekani et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using N budgets have identified raspberry fields as important sources of NO 3 –N leaching to the ASA, with isotopic signatures of the NO 3 –N indicating poultry manure as an important N source (Wassenaar, 1995; Wassenaar et al, 2006; Zebarth et al, 1998). Two studies have quantified groundwater NO 3 –N loading from individual raspberry fields in the ASA using groundwater methods (Kuipers et al, 2014; Malekani et al, 2018). However, there are currently no published studies that have quantified inter‐ and intra‐annual leaching of NO 3 –N from the root zone of raspberry over the ASA.…”
mentioning
confidence: 99%
“…Recent groundwater monitoring approaches have used vertical concentration profiles in shallow groundwater to quantify NO 3 loading from individual agricultural fields (Stites and Kraft, 2001; Kuipers et al, 2014; Malekani et al, 2018). Malekani et al (2018) successfully quantified annual NO 3 loading from an individual raspberry field over the ASA by combining high‐resolution NO 3 concentrations with volumetric groundwater flux estimated using Darcy's law. Passive diffusion samplers were used to measure NO 3 concentrations with depth at the down‐gradient edge of a raspberry field.…”
mentioning
confidence: 99%
“…The strength of this approach is that it integrates spatial and temporal variations to produce a robust estimate of N losses over larger spatial (field‐scale) and temporal (annual) scales. Thus, the approach of Malekani et al (2018) can be applied to examine the interannual effect of raspberry field renovation on NO 3 loading to groundwater in the ASA.…”
mentioning
confidence: 99%
See 1 more Smart Citation